A novel system for off-line 3D seam extraction and path planning based on point cloud segmentation for arc welding robot. (August 2020) - Yang, Lei; Liu, Yanhong; Peng, Jinzhu; Liang, Zize
Highlights: A coded structured light sensor is designed to realize 3D reconstruction of welding workpiece. Fusion the 3D structure of workpiece, a novel seam extraction algorithm is proposed based on point cloud segmentation. The path and pose mode of weld seams are solved by the established mathematical models. The proposed method has better robustness on the materials of workpieces, scratch and rust. Abstract: Due to ever increasing precision and automation demands in robotic welding, the automatic and robust 3D seam extraction has become a research hot-spot of the welding robots. At present, most of the research work about seam extraction is aimed at butt joints. Nevertheless, too little work has been devoted to fillet joints and lap joints. Consequently, to achieve robust 3D seam extraction of different weld seams, a novel seam extraction system is proposed according to the 3D structures of welding work pieces. Firstly, a fringe projection system based on Digital Light Processing(DLP) projector is designed to measure the appearance of welding work pieces. Secondly, fusion of the shape information of welding work piece, a 3D seam extraction algorithm is proposed based on point cloud segmentation. Finally, according to the space structure of weld seams, the 3D seam path model and pose estimation are solved based on the established mathematical model of weld seams. Experiments show that the proposed algorithm could well solve different weld seams, such as fillet joints, butt joints and lap joints. Meanwhile, it could well overcome the influence of the materials of welding work pieces, scratch and rust.